1993
DOI: 10.1073/pnas.90.4.1604
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of T cells by antigenic peptide complexed with isolated chains of major histocompatibility complex class II molecules.

Abstract: Major histocompatibility complex (MHC) class II molecules are heterodimeric glycoproteins with one a and one ,B polypeptide chain of similar molecular size. In this report, we describe the binding of an acetylated N-terminal peptide of myelin basic protein, , to purified individual a and 13 chains of murine I-Ak molecules. Purified complexes of isolated single chains and antigenic peptide bind to cloned T cells restricted by I-Ak and tetradecapeptide. The binding is blocked by a/13 anti-T-cell receptor (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A membrane fraction was prepared from HPAECs according to methods reported previously, with modifications [36]. Briefly, 5 × 10 7 HPAECs were washed three times with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…A membrane fraction was prepared from HPAECs according to methods reported previously, with modifications [36]. Briefly, 5 × 10 7 HPAECs were washed three times with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, human T cell clones derived from a myasthenic patient showed similar tendencies to undergo programmed cell deaths upon exposure to human DR4.AChRa peptide complexes. '•* Similarly, apoptosis was observed in a murine T cell clone restricted for IA** and rat MBP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) peptide (B. Nag, unpubl.…”
Section: Discussionmentioning
confidence: 92%
“…Each subunit consists of a short cytoplasmic tail, a single membrane‐spanning sequence, and two extracellular domains. X‐ray crystallographic studies have demonstrated that peptides from processed antigen bind to MHC molecules in the membrane distal pocket formed by the β1 and α1 domains 13, 14. Moreover, the β2 domain contains a CD4 binding region that co‐ligates CD4 when the α1 and β1 domains with associated antigenic peptide interact with the TCR αβ heterodimer, whereas the α2 domain appears to contribute to ordered oligomerization in T cell activation 15.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of MHC/antigen have been purified as detergent extracts of lymphocyte membranes,16 and as associated recombinant proteins using baculovirus and bacterial expression systems 17–21. These two‐chain, four‐domain molecular complexes, after loading with selected peptide epitopes, have been demonstrated to interact with T cells in an antigen‐specific manner 13, 14, 19, 22–24. In some cases, in the absence of co‐stimulation, these complexes induced antigen‐specific apoptosis rather than anergy 20.…”
Section: Introductionmentioning
confidence: 99%